Awake Open Atypical Gastric Resection under Combined Lumbar Spinal Anesthesia and Thoracic Epidural Neuroaxial Block in a High-Risk Patient - Manuel Wenk; Christina Massoth; Daniel Pöpping; Michael Möllmann (Global Journal of Anesthesiology - Peertechz Publications, 2017)
Modern day general anesthesia has a convincing safety record in any age group presenting with or without severe co-morbidities, hence allowing surgeons to introduce a broad range of patients to surgical procedures. However, sometimes patients present with the most signifi cant co-morbidities and organ function impairment where then general anesthesia becomes a major risk in itself. Awake surgery under regional/neuroaxial anesthesia is a possible alternative in chosen cases and has been described in cardiac and lower abdominal surgery. In this report we describe the case of a 70yr old male patient with severe chronic obstructive pulmonary disease (GOLD Stage IV) under continuous oxygen home therapy who was scheduled for open atypical gastric resection. We present the management of this case as awake surgery with the combination of a lumbar spinal anesthesia and a thoracic epidural catheter block. The combination of a lumbar spinal and a thoracic epidural anesthesia technique up to a T2-4 level can be safely used to provide sufficient segmental block for upper abdominal surgery in a high risk patient. No additional sedative and analgesic medication was required. Although thoracic epidural block may decrease intercostal muscle activity, this did not cause any major respiratory impairment.